Authentic leadership traits, high-performance human resource practices and job performance in Pakistan. Issue 3 (24th July 2020) - Zeb, Ali; Rehman, Fazal ur; Imran, Muhammad; Ali, Muazam; Almansoori, Rawdha Ghareeb
Abstract : Purpose: This empirical study aims to explore the linkage among authentic leadership traits and job performance via the mediating role of high-performance human resource practices (HPHRPs) in a developing country context. Social exchange theory and trait theory are widely employed in many disciplines but seldom applied to job performance among Pakistan Telecommunication Company Limited (PTCL) employees. Design/methodology/approach: The sample of the study is PTCL's employees. A cross-sectional design was employed and data was collected from 377 employees via questionnaire. This is an exploratory study; therefore, partial least square–structural equation modeling (PLS-SEM) was employed to answer the research questions. Findings: The findings of this study revealed that relational transparency, directly and indirectly, influenced job performance with the partial mediating role of selective staffing and extensive training. Furthermore, balance processing, directly and indirectly, influenced job performance with the partial mediating role of incentive reward, while self-awareness, internalized moral perspective, employment security and result-oriented appraisal were insignificant influences on job performance. Practical implications: The results of the study delineated practical applications for both the researchers and policymakers. The results of this study would also augment the body of knowledge on human resource practices in both developed and developing countries. Originality/value: This study found and reported authentic leadership traits and HPHR as the main sources of job performance in PTCL. This study empirically examined the influence of authentic leadership traits on job performance with the mediating role of a bundle of HPHRPs in a developing context.